2004
DOI: 10.1292/jvms.66.1595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitin and Chitosan on Collagen Synthesis in Wound Healing

Abstract: ABSTRACT. Collagen synthesis was evaluated by measuring prolyl hydroxylase (PHL) activity induced within rat granulation tissue by a polyester non-woven fabric (NWF, 1 × 1 cm, 0.6 mm in thickness) impregnated with a chitin or chitosan suspension ranging in concentration from 0.1 to 10 mg/ml. In addition, PHL activity induced in rat granulation tissue by a NWF impregnated with a phosphate buffer solution was examined as a control. The PHL activity in each group remained low until 4 days post-implantation (Day 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 16 publications
0
81
1
2
Order By: Relevance
“…Macrophages, fibroblast and vascular tissue together enter to the wound and begin to make the formation of granulation tissue that further to re-epithelialization process. 3 Kojima et al 8 reported that many polykaryocytes from the fusion of macrophages were observed in implant with chitin at 7 days compared to the control group. Chitin at higher concentration stimulate platelets and macrophages, resulting in the release of PDGF and TGF-β but the phenomenon suggests influence locally only, not systematically.…”
Section: A B C Dmentioning
confidence: 98%
See 2 more Smart Citations
“…Macrophages, fibroblast and vascular tissue together enter to the wound and begin to make the formation of granulation tissue that further to re-epithelialization process. 3 Kojima et al 8 reported that many polykaryocytes from the fusion of macrophages were observed in implant with chitin at 7 days compared to the control group. Chitin at higher concentration stimulate platelets and macrophages, resulting in the release of PDGF and TGF-β but the phenomenon suggests influence locally only, not systematically.…”
Section: A B C Dmentioning
confidence: 98%
“…6,7 Several studies report the effects of chitin and chitosan on tissue reaction involved in wound healing. 3,4,8,9 They accelerate infiltration of inflammatory cells, stimulate angiogenesis, induce the rapid formation of vascular granulating tissue, the disappearance of purulence and they promote skin regeneration with minimal scar formation. They also have candidacidal and bactericidal activity.…”
Section: Research Report Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemostasis material, medical dressing, hydrogel, drug delivery carrier, gene transfer [22] Biocompatibility, antimicrobial, innocuous, easily degradable, adsorbability, film formation [23][24][25][26][27] Poor spinnability, poor strength, low water-solubility [23,25] Starch Hemostasis material, tissue-engineered scaffold, drug delivery carrier, bone repair material [28,29] Extensive sources, low price, degradation products safe and non-toxic, non-antigenic [28,30] Poor mechanical properties, resistance to water, poor blocking performance [28,30] Alginate Pharmaceutical excipient, pepcid complete, medical dressing [31][32][33][34][35] Hypotoxicity, biocompatibility, suppresses tumor growth, enhances immunity [31][32][33][34][35] Bad biodegradability, cell attachment poor [31][32][33][34][35] Cellulose Pharmaceutical adjuvant [28] Extensive sources, low price [28] Rare adverse reactions [28] Drug-delivery carrier, tissue engineering material [36][37][38] Biodegradable, safe, non-toxic, good physical and chemical properties [37,39] High crystallinity, bad thermal stability [37,39] Chemosynthes material (Copolymer)…”
Section: Chitosanmentioning
confidence: 99%
“…However, the performance of derivatives is often better than chitosan [53]. There are many studies on chitosan derivatives obtained through such processes as acylation, alkylation, sulfation, hydroxylation, quaternization, and carboxymethylation [23][24][25][26][27]. Among them, products obtained through quaternization and carboxymethylation have received increasing amounts of attention because of their good water solubility.…”
Section: Natural Polymer-based Nanomaterialsmentioning
confidence: 99%